2008
DOI: 10.3748/wjg.14.7107
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human papillomavirus in esophageal squamous papillomas

Abstract: This study provides identification of HPV infection in almost 80% of ESP using either ACISH or PCR; overall, all of these lesions show low expression of cell-cycle markers. We suggest ACISH as an alternative diagnostic tool for HPV detection in ESP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 19 publications
5
34
2
5
Order By: Relevance
“…As described by Talamini et al (2000), ESCP did not represent a risk of development of malignancy. In agreement with them, Bohn et al (2008) found prevailing HPV infection by lowrisk types, with no association with dysplastic changes or malignant transformation. Nevertheless, Syrjänen & Syrjanen (2012) described that, similarly to cervical cancer development, there are no doubts that ESCC develops through distinct precursor lesions, namely ESCP but no prospective follow-up study has been published till now.…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…As described by Talamini et al (2000), ESCP did not represent a risk of development of malignancy. In agreement with them, Bohn et al (2008) found prevailing HPV infection by lowrisk types, with no association with dysplastic changes or malignant transformation. Nevertheless, Syrjänen & Syrjanen (2012) described that, similarly to cervical cancer development, there are no doubts that ESCC develops through distinct precursor lesions, namely ESCP but no prospective follow-up study has been published till now.…”
Section: Introductionsupporting
confidence: 83%
“…Recently, epigenetic modification of p16INK4A by hypermethylation has been implicated in cancer development, leading to gene silencing of tumor suppressor proteins (Bohn et al 2008). Our results pointed to a methylated host DNA.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Esophageal squamous papillomas (ESPs) are uncommon benign lesions, usually asymptomatic and often discovered as incidental findings. The role of HPV in these benign lesions is controversial, with a wide variation in prevalence ranging from 0 to 100% having been reported in several studies (5). As suggested by Odze et al (6), the detection of HPV in ESPs may be of a great value in terms of the follow-up of lesions associated with genotypes implicated in the genesis of premalignant and malignant lesions in squamous epithelial-lined tissues, including the nasal cavity, pharynx and anogenital tract.…”
mentioning
confidence: 99%